Gradient core-shell microstructure in mixed valence multiferroic: TM (Ti, Nb, W) substituted bismuth ferrite - Jha P.K.; Jha P.A.; Kumar P.; Asokan K.; Dwivedi R.K. (My University, 2025)
In order to study the effect of aliovalency substitution, Ti (+4), Nb (+5) and W (+6) substituted bismuth ferrite specimens have been synthesized. The multiphase XRD pattern has been obtained and there is systematic variation in the intensity of second phase XRD peak with aliovalency. But SEM microstructures are almost single phase and this dragged to analyze the microstructural variation of constituents. These observations led to the possibility of mixed/complex type microstructure model named, gradient core shell microstructure as evident by the impedance and magnetic studies. © 2016 Elsevier B.V.